Ductile rupture of aluminum sheet materials - Besson, Jacques; Brocks, Wolfgang; Chabanet, Olivier; Steglich, Dirk (European Journal of Computational Mechanics, 2001)
This study deals with ductile tearing of Aluminum 2024 sheets. Tensile tests were conducted on smooth and notched specimens. They show that the plastic behavior is anisotropie. The crack path is slanted on moderately notched specimens whereas a normal to slant fracture transition is observed on severe/y notched samples. The damage behavior is mode led using the Rousselier mode/ extended to account for plastic anisotropy. ft is shawn that the stress triaxiality can reach values up to 1.6. This shows, rogether with the slanted crack path, the importance of a 3D modeling. As the se calculations require a large computational capacity, a relative/y coarse mesh was used so thal the load is overestimated. The experimental load could be reproduced changing the material parameters; in this case normal fracture is obtained. A finer mesh should be used to obtain simultaneously the correct crack path and load. To mode/ cracking in large structures, a 2D plane stress cohesive zone mode/ is used.